Wetting and adhesion evaluation of cosmetic ingredients and products: correlation of in vitro–in vivo contact angle measurements. (28th March 2017) - Capra, P.; Musitelli, G.; Perugini, P.
Abstract: Objective: The aim of this work was to use the contact angle measurement in order to predict the behaviour of ingredients and finished cosmetic products on skin to improve skin feel and product texture. Method: Different classes of cosmetic ingredients and formulations were evaluated. The contact angle measurements were carried out by the sessile drop method using an apparatus, designed and set up in laboratory. Glass, Teflon and human skin were the reference substrates. In a preliminary phase, TEWL parameter, sebum content and hydration of human skin were measured to set up method. Results: Data demonstrated that glass substrate may be used as replacement of the skin:critical surface tension of skin and glass were about of 27 and 31 dyne cm −1, respectively. Non‐ionic surfactant with increasing HLB was evaluated: a correlation between contact angle measured and HLB was not observed because of different and complex molecular structure. In detail, ethylhexyl hydroxystearate ( θ glass = 17.1°) showed lower contact angle value with respect to Polysorbate 20 ( θ glass = 28.1°). Sodium laureth sulphate and stearalkonium chloride were also evaluated: anionic molecule showed more affinity for glass with respect to Teflon ( θ glass = 21.7° and θ Teflon = 52.3°). Lipids and silicones showed different affinity for substrate according to hydrophilic groups and hydrocarbon chain: contact angles of silicones remained unchanged independently from substrate. Finished cosmetic products (O/W, W/O emulsions, cleansing oil, dry skin oil) showed different profiles according to surfactant and its affinity for continuous phase of the formulation. Comparing the values of the contact angle on skin of non‐ionic surfactants, as ethylhexyl hydroxystearate and Polysorbate 20, they showed values lower (near to zero) than ones of sodium laureth sulphate and Stearalkonium Chloride (21.7° and 66.8°, respectively). Finally, finished cosmetic products tested on human skin showed different profile: corresponded contact angle values were less than 20°. The product tended to be quickly adsorbed on human skin. Conclusion: Systematic study carried out by evaluating the wettability of single cosmetic ingredients on different substrates allowed to find correlations between the use of certain ingredients and the final performance of a cosmetic product. Abstract : The wetting profile of non ionic surfactants on three different substrate: glass, Teflon and skin.